Reading Shakespeare's mind - Sohmer, Steve (Stephen T.); Project Muse. (Manchester : Manchester University Press, 2017)
An accessible, enjoyable, occasionally speculative study based on a vast amount of research into some of Shakespeare's more uninterpretable moments.
Preface : impersonal Shakespeare -- Part I. Shakespeare, lovers, and friends. Joining the mice-eyed decipherers -- Marlowe's ghost in As You Like It -- The dark lady of The Merchant of Venice -- Part II. Queen Elizabeth's Twelfth Night. Twelfth Night on Twelfth Night -- Shakespeare's Twelfth Night wordplay -- Shakespeare and Paul in Illyria -- Nashe and Harvey in Illyria -- M.O.A.I. deciphered at last -- Beginning at the beginning -- Tributes private and public -- Epilogue : personal Shakespeare.
Description based on print version record.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616 -- Psychology; Shakespeare, William, -- 1564-1616 -- Friends and associates; Shakespeare, William, -- 1564-1616 -- Friends and associates; Shakespeare, William, -- 1564-1616 -- Psychology; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Psychology; Friendship; Personality in literature; DRAMA -- English, Irish, Scottish, Welsh; HISTORY -- Historiography; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Shakespeare; Shakespeare Studies & Criticism; Literature & Literary Studies; Personnalite dans la litterature; Personality in literature; Criticism, interpretation, etc; Electronic books